2021
DOI: 10.21608/ejhm.2021.156457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MIF as a Diagnostic Biomarker in Cases with Ankylosing Spondylitis

Abstract: Background: Ankylosing spondylitis (AS) has been afflicting humankind as far back as ancient Egypt. Macrophage migration inhibitory factor (MIF) appears to have the unique ability to drive both inflammation and new bone formation and could play an important role in the pathogenesis of AS. Objective: The study aimed to evaluate MIF as a diagnostic biomarker in AS. Patients and Methods: This study was conducted on 42 subjects; 21 AS cases and 21 controls. Patients were subjected to full medical history, general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…19 On the other hand, there was no difference in HLA-B27 carriage between the patient and control groups (p > 0.05) in another previous similar study. 20 Additionally, other studies reported lack of association between two HLA-B27 subtypes, HLA-B*27:06 and HLA-B*27:09, with AS disease and they attributed the development of AS to genes located outside of the major histocompatibility complex locus such as loci of the IL-23/IL-17 axis, tyrosine kinase 2, signal transducer and activator of transcription (STAT) 3, IL6R, IL27, as well as several aminopeptidase genes. 8,21,22 These demonstrate the complex immunopathogenesis of the disease where multiple immunologic mechanisms contribute together to disease production.…”
Section: Discussionmentioning
confidence: 99%
“…19 On the other hand, there was no difference in HLA-B27 carriage between the patient and control groups (p > 0.05) in another previous similar study. 20 Additionally, other studies reported lack of association between two HLA-B27 subtypes, HLA-B*27:06 and HLA-B*27:09, with AS disease and they attributed the development of AS to genes located outside of the major histocompatibility complex locus such as loci of the IL-23/IL-17 axis, tyrosine kinase 2, signal transducer and activator of transcription (STAT) 3, IL6R, IL27, as well as several aminopeptidase genes. 8,21,22 These demonstrate the complex immunopathogenesis of the disease where multiple immunologic mechanisms contribute together to disease production.…”
Section: Discussionmentioning
confidence: 99%